Formulation and Development of a Water-in-Oil Emulsion-Based Luliconazole Cream: In Vitro Characterization and Analytical Method Validation by RP-HPLC - Vijay Kumar Panthi; Utsav Nepal (International Journal of Analytical Chemistry)
Luliconazole (LCZ) is a new antifungal agent containing imidazole moiety which revealed broad-spectrum antifungal activity. The aim of this research was to prepare water-in-oil (w/o) emulsion-based cream formulation of LCZ in addition to the development and validation of an analytical method by reverse-phase high-performance liquid chromatography (RP-HPLC). Cetostearyl alcohol (12.14%), light liquid paraffin (5.00%), white soft paraffin (2.75%), and Tween-80 (1.00%) appeared as the optimized concentration to give better consistency to the cream. Moreover, without adding pH adjusting agents the pH of the optimized formulation (F5) was obtained within the range of human skin pH throughout the stability period. The value of particle size, polydispersity index, and zeta potential was 187.90 ± 2.061 nm, 0.124 ± 0.026, and -10.553 ± 1.349 mV, respectively. In this study, an analytical C18 (4.6 mm × 25 cm), 5 μm column was used for chromatographic separation with a mixture of acetonitrile and water in the proportion of 50 : 50 v/v as the mobile phase at a flow rate of 1.0 mL/min. The calibration curve was obtained linear at 296 nm in the concentration range of 0.08–0.12 mg/mL. Furthermore, the limit of detection (LOD) and limit of quantification (LOQ) were 0.0013 and 0.0042 µg/mL, respectively. In addition, the observed results demonstrated that our developed method was linear (R2 = 0.999), precise (%RSD below than 2.0%), and accurate (mean recovery% = 100.18–100.91). The F5 showed no physical changes until 6th month analysis at room temperature and accelerated conditions. Similarly, the assay obtained 101.99% ± 0.27 and 99.89% ± 0.08 at room temperature and accelerated conditions, respectively. Additionally, all validated parameters were obtained within the acceptable limit as well. These findings conclude that both physically and chemically stable w/o cream formulation of LCZ can be formulated and assessed for their stability by applying the authenticated analytical procedure of RP-HPLC.